A simple strategy for tridoped porous carbon nanosheet as superior electrocatalyst for bifunctional oxygen reduction and hydrogen evolution reactions. (June 2020) - Wang, Yinghua; Wang, Shujin; Li, Ruiqing; Li, Haibo; Guo, Zengjing; Chen, Baoli; Li, Rui; Yao, Qingxia; Zhang, Xianxi; Chen, Hongyan; Li, Ying; Qu, Konggang; et al.
Abstract: The oxygen reduction and hydrogen evolution reactions (ORR/HER) play vital roles in renewable energy conversion devices but the costly Pt-based electrocatalysts greatly restrain the widespread proliferation of related technologies. Multiple heteroatom-doped carbons have aroused extensive interests due to the synergistic effect of dopants and thus multi-functional active sites. Herein, through a simple "mix-and-pyrolyze" strategy, the low-cost and nontoxic zinc pyrithione and phytic acid are explored to fabricate nitrogen, phosphorus, and sulfur-tridoped porous carbon materials, featuring a honeycomb-like nanosheet structure with a high surface area of 711.6 m 2 /g and high-level dopants including especially 6.61 at% phosphorus. In this "complicated" doping system, 95.2% N exists as graphitic and pyridinic moieties with 92.2 at% phosphorus as P–C bond, all of which are desired active sites for electrocatalysis. Accordingly, the newly-designed carbon material shows superior alkaline ORR performance with a half-wave potential of 0.91 V (vs reversible hydrogen electrode) compared with that of 20% Pt/C (0.87 V) as well as excellent acidic ORR activity. Meantime, its HER performances in both acidic and alkaline conditions are comparable to the benchmarkers. The outstanding bifunctional activity in tri-doped carbons can be attributed to the multiple active sites, large surface area, abundant porous structure and excellent charge-transfer ability. Graphical abstract: Through a simple "mix-and-pyrolyze" strategy, the low-cost and nontoxic zinc pyrithione and phytic acid are first explored to fabricate nitrogen, phosphorus, and sulfur-tridoped porous carbon nanosheet, which exhibits an alkaline ORR performance surpassing commercial Pt/C and also excellent acidic ORR performance as well as the acidic and alkaline HER activities comparable to the benchmarked MoS2 . Image 1